Evaluation of the efficacy of insecticidal coatings based on teflutrin and chlorpyrifos against Rhynchophorus ferrugineus. Issue 8 (22nd February 2017) - Pugliese, Massimo; Rettori, Andrea Alberto; Martinis, Roberto; Al‐Rohily, Khalid; Velate, Suresh; Moideen, Mohamed Ashraf; Al‐Maashi, Ali
Abstract: BACKGROUND: The date palm ( Phoenix dactylifera L.), an important economic resource for many nations worldwide, has recently been threatened by the presence of different insect pests, like the red palm weevil (RPW) Rhynchophorus ferrugineus . RESULTS: Two products, a glue (polyvinyl acetate) and an oil (raw linseed oil) were used as coatings and applied together with a repellent and two insecticides (teflutrin and chlorpyrifos) at different dosages on two species of palm ( P. dactylifera and P. canariensis ). Phytotoxic effects of the treatments were evaluated in a greenhouse on 260 potted palms (130 P. dactylifera and 130 P . canariensis ) and no negative effects were observed. Afterwards, a trial lasting 400 days was carried out in a nursery located in Sicily (south Italy), treating 572 potted palm trees (286 P. dactylifera and 286 P. canariensis ) with an average diameter at the base of 18–20 cm. After 400 days, 48% of the untreated palms were infested, while only 3% of date palms and 7% of Canary palms treated with insecticide at lower dosages were infested. CONCLUSIONS: The application of an insecticide‐based coating is a good strategy to control and prevent the red palm weevil infestation, in particular on date palms. © 2017 Society of Chemical Industry